Tantangan Aparat Penegak Hukum dalam Menangani Cybercrime di Indonesia: Kesenjangan Kapasitas, Regulasi, dan Kerjasama Lintas Batas - Gilang Rizki Aji Putra (UIN Jakarta, 2024)
Cybercrime has evolved into a sophisticated, transnational, and rapidly mutating form of criminality driven by technological advancement. Law enforcement agencies, as the frontline actors in combating these offenses, face complex multidimensional challenges. This article aims to comprehensively identify and analyze the challenges encountered by Indonesian law enforcement authorities—particularly the Police, the Prosecutor’s Office, and related institutions—in addressing cybercrime. Employing a normative-sociological legal research method with statutory, conceptual, and case study approaches, the study reveals three principal clusters of challenges: (1) technical and human resource capacity gaps that lag behind technological developments; (2) procedural regulatory frameworks that remain insufficiently adaptive to modern cyber investigations; and (3) jurisdictional barriers and limited international cooperation in pursuing transnational offenders. Analysis of major cases, including ransomware attacks, cross-border online fraud syndicates, and dark web investigations, demonstrates persistent institutional constraints. The article concludes that comprehensive institutional reform, technological investment, and enhanced international collaboration are imperative. Keywords: Law Enforcement Agencies, Cybercrime, Technical Capacity, Jurisdiction, International